Evaluation of soil and water management problems and their impact on the deterioration of date palm cultivation and productivity and the increase in desertification severity in southern Basrah - Alhamd, Abdulrahman D. (Basrah Journal Of Date Palm Research, 2023)
The study was conducted in the south of Basrah /within the districts of Abi Al-Khasib and Al-Faw during the 2021 season, to study the effect of soil and water salinization on the deterioration of date palm groves and the resulting increase in the severity of desertification in the region. Six date palm groves were selected in six locations within the study area. Four date palm trees of the Al-Halawi variety were selected in each of the study locations, so that the total number of trees would be 24 trees. The irrigation method used was the traditional method prevailing in the region (tidal flow). Soil samples were taken at the beginning and during the experiment at a depth of 0-30 cm from the studied sites with three replications for the purpose of conducting field measurements and various laboratory analyses Fruit samples were collected at the end of the season, at a rate of 15 fruits per palm tree, randomly and with four replications, to measure some physical and chemical characteristics, including dry matter percentage, weight of the fleshy layer, fruit length, and palm production rate.The results showed that the salinity of the water used for irrigation ranged between medium and very saline (4.80 and 22.14 ds m-1), while the salinity of the ground water ranged between (9.22 and 54.17) ds m-1. The results showed that the high water salinity caused problems and an increase in some aspects of desertification, the most prominent of which was the high values of soil salinity in the study area between (19.13 and 122) ds m-1, As well deterioration in the orchards of palm cultivation and a decrease in the average plant density (7 palm trees dunum-1) and a decrease in the rate of some productive characteristics such as the length of the fruit, the weight of the fleshy layer, the percentage of dry matter and the rate of production of one palm tree. The results also showed that the severity of desertification and the deterioration of date palm cultivation increased southwards towards the Faw region.